Analysis of Lead Carboxylates and Lead-Containing Pigments in Oil Paintings by Solid- State Nuclear Magnetic Resonance. Issue 1656 (18th July 2014) - Catalano, Jaclyn; Yao, Yao; Murphy, Anna; Zumbulyadis, Nicholas; Centeno, Silvia A.; Dybowski, Cecil
ABSTRACT: Soap formation in traditional oil paintings occurs when heavy-metal-containing pigments, such as lead white, 2Pb(CO3 )2 ·Pb(OH)2, and lead-tin yellow type I, Pb2 SnO4, react with fatty acids in the binding medium. These soaps may form aggregates that can be 100-200 μm in diameter, which swell and protrude through the paint surface, resulting in the degradation of the paint film and damage to the integrity of the artwork. In addition, soap formation has been reported to play a role in the increased transparency of paint films that allows the painting support, the preparatory drawing, and the artists' alterations to become visible to the naked eye. The factors that trigger soap formation and the mechanism(s) of the process are not yet well understood. To elucidate these issues, chemical and structural information is necessary which can be obtained by solid-state 207 Pb, 119 Sn, and 13 C nuclear magnetic resonance (NMR). In the present study, a combination of 207 Pb NMR pulse sequences was used to determine accurately the NMR parameters of lead-containing pigments and lead carboxylates known to be involved in soap formation, such as lead palmitate, lead stearate, and lead azelate. These results show that the local coordination environment of lead azelate is different from lead palmitate or lead stearate and therefore it is unlikely that lead azelate would be incorporated into an ordered structure containing lead palmitate and lead stearate. In addition, the chemical shifts of the pigments obtained are different from those of the soaps, demonstrating that 207 Pb NMR is useful in characterizing the components when present in a mixture, such as a paint film. The NMR methods discussed can also be applied to other Pb-containing cultural heritage materials, electronic and optoelectronic materials, superconducting materials, and environmentally contaminated materials.